Pendampingan Pembelajaran Mendalam Melalui Pembelajaran Sains dan Seni Pada Pos PAUD Cendekia Mandiri Tambakaji Kota Semarang - Rofian; Mudzanatun; Fine Reffiane; Yosi Gumala (Kreasi: Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2026)
This community service initiative was conducted to foster an understanding of deep learning within the context of early childhood education. Deep learning at the early childhood level is grounded in three core principles: mindful learning, meaningful learning, and enjoyable learning. The initiative employed a Participatory Action Research (PAR) approach, comprising demonstrations, mentoring, and discussions. The results indicate that both teachers and parents of early childhood students improved their skills and understanding regarding deep learning practices. Deep learning in early childhood settings can be implemented through hands-on science activities with students; such activities facilitate the development of awareness, the discovery of meaning in learning, and an enjoyable understanding of scientific concepts. Integrating the arts into instruction fosters "joyful" and mindful learning experiences for early child students. With effective guidance from teachers and parents, students find it easier to discover meaning in their studies and grasp the significance of the learning process. Collaborative roles played by teachers and parents enable students to effectively comprehend the nature of meaningful learning. Deep learning is essential for early childhood students as it helps build conceptual understanding, a sense of meaning, learning awareness, and an enjoyable educational experience